2013
DOI: 10.1016/j.ejca.2013.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcomes in colorectal cancer: Where do we go from here?

Abstract: Colorectal cancer (CRC) places a considerable burden on individuals and society in Europe, being the second most common cause of cancer-related death in the region. While earlier diagnosis and advances in treatment have considerably improved survival in recent years, further progress is needed. One of the greatest challenges associated with the treatment of CRC is the fact that current therapies for advanced disease are not curative, necessitating treatment for many years and placing a significant healthcare b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 64 publications
0
37
1
Order By: Relevance
“…5D). Although the detailed mechanisms of what exactly EGF binds to, how ErbB4 assists in processing KITENIN-bound phospho-Dvl2, and how lowered phospho-Dvl2 within the KITENIN/ ErbB4 complex stabilizes c-Jun are unknown, the downstream signal of EGF, the KITENIN/ErbB4-Dvl2-c-Jun pathway, that we identified in this study differs from the previously reported downstream pathways of EGF that require binding to EGFR (3)(4)(5)(6). Thus, we have identified a new EGFR-independent promotility signal of EGF in colorectal cancer cells.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…5D). Although the detailed mechanisms of what exactly EGF binds to, how ErbB4 assists in processing KITENIN-bound phospho-Dvl2, and how lowered phospho-Dvl2 within the KITENIN/ ErbB4 complex stabilizes c-Jun are unknown, the downstream signal of EGF, the KITENIN/ErbB4-Dvl2-c-Jun pathway, that we identified in this study differs from the previously reported downstream pathways of EGF that require binding to EGFR (3)(4)(5)(6). Thus, we have identified a new EGFR-independent promotility signal of EGF in colorectal cancer cells.…”
Section: Discussioncontrasting
confidence: 53%
“…S8A). To examine whether the expression levels of KITENIN affected the survival of colorectal cancer cells in response to cetuximab, we first chose Caco2 colorectal cancer cells, a KRAS/BRAF wild-type cell line (23), as these would be suitable models for the clinical setting where EGFR-targeted therapy is used (5,6). Although there was no difference in survival to cetuximab between empty vector-and KITENIN-transfected Caco2 cells, highly KITENIN-expressing Caco2 cells were resistant to cetuximab, whereas KITENIN-knockdown Caco2 cells showed increased sensitivity (Supplementary Fig.…”
Section: The Egf-kitenin/erbb4-c-jun Axis Upregulates Colorectal Cancmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of transfection was assessed by fluorescence microscopy (Helmut Hund GmbH, Wetzlar, Germany) of GFP-tagged UBE2Q1 protein, and confirmed by western blot analysis. The selection medium was replaced every 3 days, and individual clones (7)(8) were isolated and propagated 21-28 days post-transfection. These clones were isolated as stable transfectants.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of improvements in diagnosis and adjuvant therapy of CRC (7)(8)(9), the mortality rate for CRC is still ~40% (10). Therefore, a critical study for uncovering the biological mechanisms underlying the progression of CRC could lead to more efficient treatment strategies (11).…”
Section: Introductionmentioning
confidence: 99%